Morphological and cytochemical description of blood cells from raptors of the order Accipitriformes, apprehended or rescued in the Atlantic Forest biome of Rio de Janeiro (southeastern Brazil). (Research, Society and Development, 2022)
Morphological and cytochemical characteristics of the blood cells of 14 free-living accipitrids seized or rescued in the Atlantic Forest biome of Rio de Janeiro were analyzed. This study was conducted using two cytochemical staining techniques, peroxidase (PER) and Sudan black (SBB). For morphological analysis, stained blood smears were evaluated under optical microscopy. To the best of the authors' knowledge, this was the first study on blood cell morphology in Parabuteo unicinctus and the first to cytochemically evaluate blood cells from this species and from Rupornis magnirostris. As for morphology, it was found that blood cells of the evaluated animals were similar to those of other acipitrids. Heterophils were the most prevalent leukocytes. Eosinophils and lymphocytes were also observed in expressive values. Only the eosinophils of P. unicinctus showed a positive reaction to PER e SBB. The specimens of R. magnirostris showed eosinophils with positive reaction only for SBB. The other leukocytes had negative results for both PER and SBB. It was concluded that the morphological and cytochemical characteristics of P. unicinctus and R. magnirostris blood cells are similar to those of other acipitrids, except for eosinophils, which differ biochemically. In this context, the present study of cytochemical techniques can provide an important database to be accessed in future research, including the influence of eosinophil composition on the function of these cells in predators.